Hubungan antara Trait Kepribadian Neuroticism dan Self-Regulated Learning pada Siswi Pondok Pesantren “X” di Yogyakarta - Ike Zuraeni; Sara Palila (Jurnal Psikologi Integratif, 2016)
This study aims to investigate the correlation between personality trait Neuroticism and Self Regulated Learning on student at Pondok Pesantren "X" in Yogyakarta. Research subjects in this study were student of Pondok Pesantren "X" in Yogyakarta grade XI and grade XII, while the characteristics is a female student from grade XI and grade XII SMA / MA, majoring in science, and 15-20 years old. This study use quantitative research methods using the scale as a measuring tool. The first scale is the Self Regulated Learning and second scale is Neuroticism Personality Trait. The results showed that there was a negative correlation between Neuroticism Personality Trait and Self Regulated Learning on student at Pondok Pesantren "X". The higher Personality Trait Neuroticism, the Self Regulated Learning is lower. Conversely, the lower Personality Trait Neuroticism, the Self Regulated Learning is higher. Based on these results, the hypothesis proposed in this study is received, and this is indicated by the correlation coefficient (r xy) of -0.596 with p = 0.000 (p <0.01). The effective contribution of Neuroticism Personality Trait for Self-Regulated Learning on female student of Pondok Pesantren is 35.5%. It shows that the Neuroticism Personality Trait had 35.5% influence to degrade Self Regulated Learning, while the rest of 64.5% is influenced by another factors.